Review of the self-sacrifice dimension of the dimensional clinical personality inventory - Lucas de Francisco Carvalho (Psicologia: Reflexão e Crítica, 2016)
Abstract The present study aimed to review the Self-sacrifice scale from the Dimensional Clinical Personality Inventory (IDCP), and investigate its psychometric properties. To this end, the study comprised 199 participants, aging between 18 and 54 years (M= 26.37; SD= 8.13), and 142 were women (71.4 %). All subjects answered the IDCP and the Brazilian versions of the NEO Personality Inventory - Revised and the Personality Inventory for DSM-5 (PID-5). Based on the exploratory factor analysis with confirmatory indices (E-SEM), four interpretable factors were found, besides the total score for the scale reviewed. The factors showed adequate internal consistency coefficient ranging between .78 and .87. Furthermore, the correlations between the factors and the total score and the dimensions of the other instruments used were consistent, especially regarding to the PID-5. Accordingly, we conclude that the revised version size is more suitable adequate from the psychometric perspective compared to the original version, besides being more related to the pathological personality functioning.